Structure‒function‒pathogenicity analysis of C-terminal myocilin missense variants based on experiments and 3D models - Zhou, Biting; Lin, Xiaojia; Li, Zhong; Yao, Yihua; Yang, Juhua; Zhu, Yihua (Frontiers in Genetics, 2022)
MYOC is a common pathogenic gene for primary open-angle glaucoma and encodes the protein named myocilin. Multiple MYOC variations have been found, with different clinical significance. However, the pathogenesis of glaucoma induced by MYOC mutations has not been fully clarified. Here, we analyze the molecular and cellular biological differences caused by multiple variant myocilins, including protein secretion characteristics, structural changes, subcellular localization, cellular autophagy activity and oxidative stress. Denaturing and nondenaturing electrophoresis showed myocilin to be a secreted protein with the tendency to self-oligomerize. The full-length myocilin and its C-terminal cleavage fragment are secreted. Secretion analysis of 23 variant myocilins indicated that secretion defects are closely related to the pathogenicity of MYOC variants. Structural analysis showed that the alteration of steric clash is associated with the secretion characteristics and pathogenicity of myocilin variants. Immunocytochemistry results demonstrated that mutated myocilins are retained in the endoplasmic reticulum and induce autophagy disruption. MTT assay MitoTracker staining, and DCFH-DA staining showed increased oxidative injury in cells expressing MYOC mutants. Taken together, MYOC mutations are able to induce cell dysfunction via secretion defects and intracellular accumulation resulting from steric clash alterations.